The Role of Emotional Intelligence in Enhancing Workplace Performance - Babu, Stephen (AG Volumes, 2024)
Emotional intelligence is a concept that is considered to be indispensable for professional success, and it pertains to the manner in which individuals interact with their surroundings. Emotional intelligence is closely associated with the overall satisfaction of employees, who are essential to organisations. In this article review the various literature’s study on emotional intelligence in enhancing workplace performance. It concluded that emotional intelligence (EI) significantly enhances workplace performance by improving productivity, decision-making, and collaboration. This review highlights the strong link between EI and organizational productivity, with interpersonal skills and stress management playing key roles. Organizations can benefit from integrating EI into recruitment, training, and workforce development. In the public sector, EI is essential for effective service delivery. Additionally, incorporating EI into education can help bridge skill gaps. Future research can explore additional EI indicators across sectors. Overall, EI is a vital, teachable skill that should be systematically implemented to drive workplace success and organizational growth.